Reconstruction of charged tracks with Timepix4 ASICs. (1st February 2023) - Akiba, K.; van Beuzekom, M.; van Beveren, V.; Byczynski, W.; Coco, V.; Collins, P.; Dall'Occo, E.; Dumps, R.; Evans, T.; Geertsema, R.; Gkougkousis, E.L.; Halvorsen, M.M.; et al.
Abstract: The spatial and temporal performance of a four-plane system composed of silicon sensors bump-bonded to Timepix4 ASICs is assessed with a 180 GeV/c mixed hadron beam at the CERN SPS and reported in detail. Particle tracks are reconstructed using time-space measurements from the four detector planes, two 100 μm planes perpendicular to the beam and two 300 μm sensors under an angle of 9°. The spatial hit resolution is assessed to be (15.5 ± 0.5) μm and (4.5 ± 0.3) μm for 100 μm and 300 μm thick sensors, respectively. The timestamps from the detectors are also measured with fine precision, yielding time resolutions of (452 ± 10) ps, (420 ± 10) ps, (639 ± 10) ps, (631 ± 10) ps for the two 100 μm and two 300 μm thick sensors respectively. These measurements are combined to a track time resolution of (340 ± 5) ps. The design of the detector system is described together with its data acquisition system, operational infrastructure, and dedicated software.